Managing Director's Statement to the International Monetary and Financial Committee on Financing Sustainable Development-Key Policy Issues and the Role of the Fund. (Policy Papers; Policy Paper ;, 2015)
2015 is a pivotal year-a year when the international community will commit to a shared vision on goals for international development through 2030 and beyond. Achieving these Sustainable Development Goals (SDGs) will require a partnership among advanced, emerging, and developing economies, and international institutions to ensure that the required policies are put in place and that sufficient private and public resources are mobilized. The Fund, with its global membership and mandate at both the national and multilateral levels, is uniquely positioned to contribute to this compact and help implement it. As new deliverables, the IMF is considering: 1. Boosting the access to IMF resources provided to developing countries, better positioning them to handle balance of payments needs as they pursue growth; 2. Expanding diagnostic and capacity-building support for countries seeking to scale up investment to tackle infrastructure gaps; 3. Sharpening the focus of operational work on equity, inclusion, and gender, drawing on ongoing analysis and work of other institutions; 4. Increasing the focus on and resourcing of work on fragile/conflict-affected states; 5. Selective expansion of capacity-building efforts in the areas Full text is also available in French and Spanish.